Efektivitas Program Keluarga Harapan (PKH) dalam Rangka Penanggulangan Kemiskinan (Suatu Studi di Kecamatan Kota Utara Kota Gorontalo). - Usman, Claudio (Sam Ratulangi University, 2014)
ABSTRACT: Effectiveness of Program Keluarga Harapan ( PKH ) in term of the Destitution Tackling (Study in Kecamatan Kota Utara Kota Gorontalo) beneath the guidance by Drs. Jantje Mandey M.Si and Drs. Joorie M. Ruru M.SiThe large development of the citizen in Indonesia nowadays, can not be balanced with the government ability to manage and to control the people of the society maximally. It causes by a few factors, and with no coordination of each factors become one of them, the less of human resources , and the big amount of the citizen , etc. Furthermore, should not be very surprised if people of Indonesia are still live beneath of line of the destitution. There is many efforts that government did to cope this problem, such as the direct funds given by government to the people of the society, and one of them is Program Keluarga Harapan (PKH).The aim of this research is to analyze the effectiveness Program Keluarga Harapan (PKH) that can obviously resolve the destitution. This research is placed in Kecamatan Kota Utara Kota Gorontalo. The research method that used is quantitative research method with the sample are 90 respondents.The result of the research shown that the respondents opinions in Kecamatan Kota Utara Kota Gorontalo about the effectiveness Program Keluarga Harapan (PKH) averagely in the middle or moderate category, that is 46.7 % of 90 respondents, while in the low category is 23.3 % from respondents, and in the high category just around 19.1 %, whereas for the destitution tackling average being in the middle category is 48.9, while in the low category that is 14.4 % of 13 respondents and the high category around 36.7 %.Key words : Effectiveness, Program Keluarga Harapan, Destitution